SIKAP DAN PERILAKU JAVANESE TRADISIONAL HEALING MASA NIFAS PADA IBU MODERN ANTAR GENERASI - Umi Baroroh; Adevia Maulidya Chikmah (Universitas Muhammadiyah Kudus, 2023)
The healing system in Indonesia is experiencing pluralism. Where a variety of different ways of treatment exist side by side including humoral medicine and magical elements. Socio-cultural factors have an important role in understanding the attitudes and behavior of human life, one of which is in the postpartum period. The descriptions of Javanese culture in postpartum mothers obtained include pilis, parem, drinking herbal medicine, massage, stagenan, octopus, kempitan, walik dadah, sitting senden, abstinence from eating and sitting culture. This underlies the researcher to take the title of the study of Traditional Javanese Attitudes and Behaviors Healing the Postpartum Period in Modern Mothers at Harapan Bersama Polytechnic.This research is a descriptive non-experimental quantitative research, with the research design used is cross sectional. With the population of Harapan Bersama Polytechnic employees who are female and have postpartum experience as many as 55 people but who are willing to become respondents (sample) are only 44 respondents. With a measuring instrument using a questionnaire.TestAnalysisbivariate statistical test using chi square where there is no relationship between age and respondent's attitude towards Javanese Traditional Healing during the postpartum period with a significance level of 0.155 (P 0.05), there is no relationship between age and respondents' behavior towards Javanese Traditional Healing during the postpartum period with a significance level of 0.155 (P 0 0.05) and there is a relationship between attitudes and behavior of respondents towards Javanese Traditional Healing during the postpartum period where the results obtained a significance level of 0.000 (P 0.05). It is hoped that the postnatal care of Javanese culture can be monitored and made more modern so that it is not harmful to health.Keywords: Attitude, behavior, postpartum complementer